Fusion vaginal wall in a pediatric patient with post hematopoietic stem cell transplantation - Herrera Morales, Juan Carlos; Hernández Velázquez, Ricardo; Ruz Barros, Rodrigo Emilio; Flores Villegas, Luz Victoria; Guerrero Reyes, Guadalupe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Aplastic anemia is a rare condition characterized by bone marrow failure and reduced blood cell production. Hematopoietic stem cell transplantation (HSCT) is the preferred treatment when a matched donor is available. This condition carries a graft-versus-host disease (GVHD) risk, affecting 30-70% of patients. GVHD can manifest in various areas, including the mouth, skin, and genitals, with vaginal symptoms present in 26% of cases. These may include dryness, itching, discharge, and labial fusion. A 14-year-old female treated with HSCT, developed skin and vaginal GVHD. She experienced amenorrhea and abdominal pain, a subsequent MRI revealed a normal uterus but a lobed vagina with multiple septa. The patient underwent vaginal exploration and laparoscopic surgery, revealing a fusion in labia minora and a significant vaginal cavity obstruction. Approximately 600 ml of blood was drained. Female genital GVHD in pediatric patients has a low incidence of 5.9%. Symptoms often include vulvar pain (37%), dysuria (37%), and pruritus (26%), with many patients remaining asymptomatic. A study found limited occurrences of vaginal stenosis, emphasizing the rarity of severe presentations. Routine gynecological evaluations are recommended for patients post-HSCT. In cases of colpohaematometra, draining and addressing stenosis may be necessary. Vaginal GVHD is a common complication of HSCT, ranging from vulvar pruritus to severe vaginal stenosis or fusion. Management may involve surgical liberation, vaginal molds, and treatment with estrogens and corticosteroids. Gynecological consultations are recommended for all patient’s post-transplant.